Discursive (de)legitimation strategies in Malaysian news media discourse on female circumcision (sunat perempuan) - Nik Soffiya Nik Mat; Surinderpal Kaur; Stefanie Pillai (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article unpacks the discursive (de)legitimation strategies used by the Malaysian government and Malaysian civil society organisations to construct and contest the legitimacy of female circumcision in Malaysia. This paper examines the ways in which female circumcision in Malaysia is legitimised and contested within the Malaysian news media. Malaysian mainstream and alternative news articles discussing the practice that was published online between the years of 2016 and 2020 were analysed based on previous studies on legitimation (Van Leeuwen, 2008) as the main analytical tools to examine the approaches taken by the Malaysian government and Malaysian civil society organisations to (de)legitimise the practice in Malaysia. Findings reveal that the Malaysian government actively supported the practice of female circumcision using the strategies (1) authority of tradition and authority of conformity, (2) impersonal authority of adat (Malay custom), (3) personal and expert authority (4) denial of female circumcision as a form of FGM/C, (5) mitigation of harm through medicalisation, (6) moral legitimation by cultural relativism, and (7) scientific rationalisation using religion. Malaysian civil society organisations mainly countered the hegemonic discourse using the synergistic strategies of moral evaluation and rationalisation with discourses of health and human rights as the motif of resistance.